FORUM: Sharing or sparing? How should we grow the world's cities?. Issue 5 (17th June 2013) - Lin, Brenda B.; Fuller, Richard A.
Summary: There has long been a debate amongst conservation biologists about how agricultural land use should be distributed spatially. Advocates of land sparing argue that high‐intensity food production on small units of land will conserve more natural habitat than low‐intensity farming spread across larger areas. Others argue that less intensive production over a greater area of land will reduce the overall load of human stressors upon ecosystems. Although agricultural and urban systems have traditionally been considered as different fields of research, there are strong parallels between the two landscapes in the patterns of their spatial configuration and the trade‐offs associated with their development. Continued and rapid urbanization, with associated losses in vegetation, highlights the need for a uniting spatial framework to assess the ecological impacts of urbanization. Here, we apply some of the thinking emerging from the agricultural land‐sparing debate to urbanization, review the similarities and differences between the two systems and set out a research agenda. Intensification of urban systems to increase housing density leads to buildings being interspersed with small tracts of natural or semi‐natural habitat patches (e.g. forest patches, parks). Urban extensification, on the other hand, is characterized by sprawling suburbanization with less concentrated, more distributed green space, often predominantly in the form of backyard or streetscape vegetation. We argue that regional scale analyses are urgently needed to determine which of these patterns of urban growth has a lower overall impact on biodiversity and to explore the geographical and taxonomic variation in the most ecologically appropriate city layout. Synthesis and applications . The spatial pattern of urban development will affect biodiversity conservation within and beyond a city's borders. We chart the early progress of empirical work on the land‐sparing debate in an urban context and suggest that to yield development patterns that minimize overall ecological impact, urban planners must work at the scale of at least the entire city rather than on a case‐by‐case basis. Abstract : The spatial pattern of urban development will affect biodiversity conservation within and beyond a city's borders. We chart the early progress of empirical work on the land‐sparing debate in an urban context and suggest that to yield development patterns that minimize overall ecological impact, urban planners must work at the scale of at least the entire city rather than on a case‐by‐case basis.